Profil Kromatogram dan Uji Aktivitas Antibakteri Beberapa Fraksi Ekstrak Daun Kemuning (Murraya paniculata (L.) Jack) terhadap Bakteri Penyebab Disentri dengan Metode Difusi Agar - Masayu Azizah; Sri Ekawati (Faculty of Mathtmatics and Natural Sciences, 2017)
A research on the chromatogram profile and antibacterial activity of some fraction of the extract of Murraya paniculata (L.) Jack against the bacteria that cause dysentery. This study aimed to determine the pro-file of the chromatogram and antibacterial activity of some fraction of the extract of Murraya paniculata (L.) Jack against the bacteria that cause dysentery. Viscous extract obtained by maceration method and then frac-tionation. Profile chromatogram is done by thin layer chromatography separation and activity in case against several bacteria that cause dysentery performed by the agar diffusion method. The results showed that the pro-file of the chromatogram obtained Murraya paniculata (L.) Jack ethanol extract of phenolic compounds, fla-vonoids and steroids. In the water fraction obtained phenolic compounds and flavonoids. Ethyl acetate frac-tion obtained phenolic compounds. N - hexane fraction obtained steroid compounds and terpenoids. The re-sults of bacterial inhibition highest diameter obtained in ethyl acetate fraction against bacteria Shigella boydii ATCC 12985 with an average of 16.16 mm, 15.5 mm, 14.1 mm and 12.1 mm.